2012
DOI: 10.5402/2012/907102
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Time as a Predictor of Physical Recovery in the First Months after Heart Transplantation

Abstract: Functional results after heart transplantation range from modest to spectacular improvement. Little is known about factors to predict functional result. This study aimed to identify these factors. We present a prospective study including all consecutive transplant recipients (n = 55) in a two-year period whose survival was greater than two months. Perioperative, donor, and recipient issues were systematically analyzed. Exercise capacity was assessed by symptom-limited treadmill exercise testing two months afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…al., regarding donor and recipient specific qualities that impact functional recovery in the 2 months following transplant. 16 This discrepancy may be in part due to the method used to test and evaluate OHT recipients. Those investigators, used the Bruce treadmill protocol, which utilizes steep incline and speed increases each progressing stage.…”
Section: Comparison Of Results To the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…al., regarding donor and recipient specific qualities that impact functional recovery in the 2 months following transplant. 16 This discrepancy may be in part due to the method used to test and evaluate OHT recipients. Those investigators, used the Bruce treadmill protocol, which utilizes steep incline and speed increases each progressing stage.…”
Section: Comparison Of Results To the Literaturementioning
confidence: 99%
“…17 The RPE-CR10 (1 to 10) scale is a common method for determining exercise intensity levels, where "0" = nothing at all and "10" = very, very hard. The traditional Borg scale (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) was not used due to the disassociation between level of difficulty and heart rate seen in a denervated heart. Continuous blood pressure (BP) measurements were taken to ensure hemodynamic stability and lead II ECG was monitored continuously by telemetry staff.…”
Section: Cardiovascular Rehabilitation (Cr) and Prevention Center At mentioning
confidence: 99%
See 1 more Smart Citation
“…[6,7] Graft dysfunction due to prolonged donor ischemic time, which may lead to an increased need for inotropic agents as well as postoperative VAD implantation, has not only been linked to mortality but has also been connected with a decrease in the early postoperative functional capacity of recipients. [8] Several studies have also reported reduced survival rates in patients with prolonged donor ischemic time, [4,6,[9][10][11] but other studies have not shown any connection. [1,12,13] Kilic et al [11] studied 9,404 patients who underwent an orthotopic heart transplantation from 1987 to 1999 and concluded that younger patient age (<55 years), a shorter donor ischemic time, and younger donor age were the most important factors for predicting the 10-year survival rate after cardiac transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…По данным многих исследований, непосредственные и отдаленные результаты ОТС с короткой и длительной ишемией донорского сердца сопоставимы [8][9][10][11], что согласуется с нашими данными. Однофакторный регрессионный анализ не выявил влияние длительности холодовой ишемии на госпитальную выживаемость.…”
Section: результатыunclassified